2000
DOI: 10.1159/000029123
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Comorbidity among DSM-III-R Personality Disorders

Abstract: The aim of this study was to examine patterns of comorbidity among personality disorders (PDs) in a sample of 156 psychiatric inpatients. PDs were assessed with Semistructured Clinical Interview for DSM-III-R Personality Disorders. To determine significant co-occurrence among axis II diagnoses, odds ratio and the percent of co-occurrence of pairs of disorders were calculated. Both statistical methods revealed high rates of comorbidity: significance association was found for 36 pairs of disorders using the perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 12 publications
6
27
0
1
Order By: Relevance
“…Most studies are of inpatients only (40,42) or of inpatients combined with outpatients (12,13,29,41,(44)(45)(46). We are not aware of a study that is comparable to the MIDAS project in which semistructured interviews have been integrated into a community-based outpatient practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies are of inpatients only (40,42) or of inpatients combined with outpatients (12,13,29,41,(44)(45)(46). We are not aware of a study that is comparable to the MIDAS project in which semistructured interviews have been integrated into a community-based outpatient practice.…”
Section: Discussionmentioning
confidence: 99%
“…Integrating research-quality evaluations into an outpatient practice requires that more obstacles are overcome (25). Diagnostic interviewers in the studies listed in Table 4 included psychiatric residents (12,13,42), trained research interviewers with undescribed levels of experience and professional training (29,41), and psychiatrists with extensive prior experience with semistructured diagnostic interviews (45). The samples also differed in the most frequent axis I disorders and the diagnostic system used.…”
Section: Discussionmentioning
confidence: 99%
“…Within-PD comorbidity rates are high (1) in non-patient as well as patient samples (Zimmerman & Coryell, 1989), (2) using different assessment instruments (Oldham et al, 1992), and (3) across various Western cultures (Marinangeli et al, 2000). This excessive comorbidity undermines the validity and utility of the DSM-5 -II PD diagnostic system, in which the 10 PD criterion sets are intended to reflect “qualitatively distinct clinical syndromes” (APA, 2013, p. 646).…”
Section: Problems With the Current Categorical Pd Diagnostic Systemmentioning
confidence: 99%
“…In outpatient samples, rates of 9.3 to 18% have been reported, with a pooled rate of 11.9% [5]. Studies of psychiatric inpatient populations have reported rates of BPD at about 40% [9]. …”
Section: Introductionmentioning
confidence: 99%